Postmortem fertilization: New Italian government guidelines affirm the legitimacy of this procedure. - Emanuela Turillazzi; Donato Morena; Matteo Scopetti; Vittorio Fineschi (Elsevier, 2024)
Although posthumous reproduction (PHR) is viewed unfavorably by some, it may be a desirable option for subjects whose partners died before they could complete their family planning. With particular regard to posthumous embryo implantation, questions arise regarding the definition of ''conception'' when a couple undergoes in vitro fertilization while both are alive, but the embryo is implanted in a woman's womb after one parent has died. In accordance with Italian Law 40/2004, access to medically assisted reproduction is contingent upon the survival of both partners in a couple. The legislative prohibition remains in effect unless the application of the reproductive technique has already resulted in the formation of embryos, and implantation is permitted to uphold ''the rights of all the subjects involved, including the conceived'', as stated in Article 1 of Law 40/2004. Since the enactment of the legislation, a number of Italian courts have issued rulings on PHR on a case-by-case basis. Recent government guidelines in Italy have sought to balance these considerations, giving due weight to the will of the woman, the potential unborn child, and the previous consent of the donor partner.